RESEARCH AND DEVELOPMENT OF A MOBILE APPLICATION INTERFACE FOR RIDESHARING FOR A UNIVERSITY CAMPUS IN AMAZONAS - Gonçalves Soares Lacerda, Cristhian; Kuwahara, Nelson; Costa Pinto da Silva, Paula; Kimura Bentes, Tiago (AEC&D - Arte, Educação, Comunicação & Design, 2020)
The worsening in the last two decades of the conditions of urban mobility in the world has aroused in contemporary societies the need to face barriers and inefficiencies in mobility in cities. With the advent of information technology in the last decade, favorable conditions have emerged for the feasibility of some mobility alternatives. In this context, there is the ridesharing method, integrating drivers and hitchhikers by the application that presents specific boarding and disembarkation routes and points associated with different gains for both and society in general. This paper presents the development of the mobile application interface design for integration between members of a university in northern Brazil. Usability guidelines applied in application interface design guided the methodology used for application development.